2012
DOI: 10.1177/003335491212700211
|View full text |Cite
|
Sign up to set email alerts
|

Examining Compliance with a Statewide Law Banning Junk Food and Beverage Marketing in Maine Schools

Abstract: Policy development is an important and powerful tool to promote health and welfare in society, yet the process of adopting policies is rarely evaluated for compliance, and studies examining policy impact sometimes neglect to verify the extent to which the policy interventions are faithful to the policy's original intent. Evaluations can lead to critical improvements and improve success in achieving intended goals. In this article, Polacsek et al. present a simple yet elegant evaluation of Maine's law to limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 7 publications
(8 reference statements)
0
33
0
Order By: Relevance
“…31 However, it appears that such policies were not sustained in city schools in recent years, perhaps because policies related to sales or advertising can garner much-needed financing for school programs. 29 While the shifts observed in the current study represent a reduction in urban/rural disparities by some measures, they also indicate an overall worsening of conditions in city schools.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…31 However, it appears that such policies were not sustained in city schools in recent years, perhaps because policies related to sales or advertising can garner much-needed financing for school programs. 29 While the shifts observed in the current study represent a reduction in urban/rural disparities by some measures, they also indicate an overall worsening of conditions in city schools.…”
Section: Resultsmentioning
confidence: 57%
“…27 This finding could reflect increased attention to the nutritional quality of food and beverages sold in vending machines and school stores, particularly in schools with younger students. Schools became less likely to ban advertisements for LNED items on school grounds (p = 0.01), suggesting an increased use of advertising for revenue 28,29 that may be used to cover basic costs and programming when financial resources are limited. 30 This shift toward increased advertising should be examined in future research, and linked to changes in school budgets and student health outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…A prior study found widespread food and beverage marketing in a random sample of 20 Maine high schools: 17 (85%) had marketing not compliant with a statewide law banning some types of food and beverage marketing. This marketing appeared throughout buildings and grounds, most often in the cafeteria, athletic areas, entrance and hallways, and teachers' lounges . This research also suggested numerous barriers to compliance with the state policy.…”
mentioning
confidence: 73%
“…Polacsek and colleagues’ examined implementation of a statewide law banning food and beverage marketing in Maine high schools [60]. Noncompliant marketing of foods and beverages was found in 85% of the high schools studied, with an average of 12 instances of noncompliant marketing per school, with most noncompliance occurring in athletic areas and teachers’ lounges.…”
Section: Resultsmentioning
confidence: 99%